Kategorie samotności i wspólnotowości w filozofii Miguela de Unamuno - Polit, Krzysztof (Filozofia Chrześcijańska, 2015)
The most important issue in our life, that everyone has to solve is relationship with the others. This article is an attempt to analyze the original views of the Spanish writer and philosopher about the importance of solitude in people’s life and in shaping their spirituality. There’s an attempt to answer the question why, according to Unamuno, the great solitaries have made more contribution to the humanity than the great leaders, inventors and politicians.